Analysis of the profitability of road freight transport in the Republic of Serbia : DOI: 10.5937/etp240424P - Peštović, Kristina; Nuševa, Daniela; Dakić, Stojanka; Đurković Marić, Tijana (Ekonomija - teorija i praksa, 2025)
This paper analyzes the profitability of companies in the field of road freight transport in the Republic of Serbia. The primary goal of the profitability analysis is to determine whether companies are profitable and to identify factors that positively or negatively influence profitability. The research sample consists of 614 observations of road transport freight companies over the period from 2006 to 2023. Profitability is measured based on return on assets, while independent variables include company size, number of days for receivables collection, liquidity, the ratio of sales revenue to total assets, and indebtedness. The research results primarily indicate that companies achieve, on average, a positive profitability of 6.54% over the observed period. Furthermore, the results of the unbalanced panel regression analysis show that liquidity, the ratio of sales revenue to total assets, and the number of days for receivables collection have a significant impact on profitability. The findings may be of interest to management, company owners, regulatory bodies, and other stakeholders in making appropriate business decisions and ensuring adequate profitability and business sustainability.